Arbuscular mycorrhizal fungi and associated microbial communities from dry grassland do not improve plant growth on abandoned field soil - Pánková, Hana; Lepinay, Clémentine; Rydlová, Jana; Voříšková, Alena; Janoušková, Martina; Dostálek, Tomáš; Münzbergová, Zuzana (Oecologia, 2018)
After abandonment of agricultural fields, some grassland plant species colonize these sites with a frequency equivalent to dry grasslands (generalists) while others are missing or underrepresented in abandoned fields (specialists). We aimed to understand the inability of specialists to spread on abandoned fields by exploring whether performance of generalists and specialists depended on soil abiotic and/or biotic legacy. We performed a greenhouse experiment with 12 species, six specialists and six generalists. The plants were grown in sterile soil from dry grassland or abandoned field inoculated with microbial communities from one or the other site. Plant growth, abundance of mycorrhizal structures and plant response to inoculation were evaluated. We focused on arbuscular mycorrhizal fungi (AMF), one of the most important parts of soil communities affecting plant performance. The abandoned field soil negatively affected plant growth, but positively affected plant response to inoculation. The AMF community from both sites differed in infectivity and taxa frequencies. The lower AMF taxa frequency in the dry grassland soil suggested a lack of functional complementarity. Despite the fact that dry grassland AMF produced more arbuscules, the dry grassland inoculum did not improve phosphorus nutrition of specialists contrary to the abandoned field inoculum. Inoculum origin did not affect phosphorus nutrition of generalists. The lower effectiveness of the dry grassland microbial community toward plant performance excludes its inoculation in the abandoned field soil as a solution to allow settlement of specialists. Still, the distinct response of specialists and generalists to inoculation suggested that they differ in AMF responsiveness.
Keywords: Mycorrhizae; Fungi; Soil biota; Soil legacy; mikrobiota; Plant Development; Plant Roots; Mycorrhizal response; houby; Soil Microbiology; Microbiota; Grassland; Soil; kořeny rostlin; Fungal structures; pastviny; půdní mikrobiologie; Native AMF; vývoj rostlin; mykorhiza; půda